Parietal Lipoma Associated with Cortical Dysplasia and Abnormal Vasculature: Case Report and Review of the Literature - Saatci, Isil; Aslan, Cengiz; Renda, Yavuz; Besim, Aytekin (American Journal of Neuroradiology, 2000)
Summary: We present the case of an unusually located intracranial lipoma in a 17-year-old patient with partial epilepsy who was being controlled with medication. The lipoma was located deep in the left sylvian fissure, in the inferior parietal lobule, associated with cortical dysplasia of the surrounding supramarginal gyrus. Abnormal vasculature was detected adjacent to and within the adipose mass. The findings of the imaging studies that included CT, MR imaging, and MR angiography, are described along with a brief review of the literature.